2019
DOI: 10.1371/journal.pone.0220877
|View full text |Cite
|
Sign up to set email alerts
|

Effects of palm oil consumption on biomarkers of glucose metabolism: A systematic review

Abstract: Introduction Vegetable oil is an important source of fatty acids, and as palm oil being the highest consumed vegetable oil in many countries, its high saturated fatty acid content has led many concerns on cardiometabolic health. Dietary fatty acids has also been linked to affect glucose metabolism and insulin sensitivity. This systematic review is aimed at critically evaluating the available evidence on the association of palm oil with the biomarkers of glucose metabolism as compared to other vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
(106 reference statements)
0
5
0
5
Order By: Relevance
“…While purchasing RSPO-certified palm oil might be an option for consumers who are concerned about the sustainability of conventional palm oil cultivation, potential health concerns might probably not be resolved in this way. Although there is still a lack of robust scientific evidence on the adverse health effects of palm oil consumption [99][100][101], many consumers still perceive palm oil as unhealthy. Potential health concerns have not been assessed in this study, but previous research suggests that such concerns might positively influence preferences for "palm-oil-free" products (e.g., [48,50,52]).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…While purchasing RSPO-certified palm oil might be an option for consumers who are concerned about the sustainability of conventional palm oil cultivation, potential health concerns might probably not be resolved in this way. Although there is still a lack of robust scientific evidence on the adverse health effects of palm oil consumption [99][100][101], many consumers still perceive palm oil as unhealthy. Potential health concerns have not been assessed in this study, but previous research suggests that such concerns might positively influence preferences for "palm-oil-free" products (e.g., [48,50,52]).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Wyniki wielu badań wskazują, że całodzienna racja pokarmowa bogata w nasycone kwasy tłuszczowe przyczynia się do wzrostu stężenia frakcji LDLcholesterolu we krwi zwiększonego ryzyka wystąpienia chorób sercowo-naczyniowych (CVD) [47]. Mimo że olej palmowy zawiera znaczne ilości nasyconych kwasów tłuszczowych, to wiele badań nie potwierdza jego negatywnego wpływu na gospodarkę lipidową.…”
Section: Wpływ Oleju Palmowego Na Parametry Lipidowe Krwi I Ryzyko Ch...unclassified
“…Wyniki badań wskazują na prodiabetogenny wpływ nasyconych kwasów tłuszczowych [2]. Dlatego postawiono hipotezę, że tłuszcz palmowy może wywierać niekorzystny wpływ na metabolizm węglowodanów [47].…”
Section: Wpływ Oleju Palmowego Na Stężenie Glukozy We Krwiunclassified
See 1 more Smart Citation
“…Schwingshackl, Strasser, & Hoffmann, 2011), one showing greater effect than PUFA (Qian et al, 2016). Replacing SFA or carbohydrate with plant-derived PUFA had a favorable albeit weak effect on glucose and insulin in predominantly healthy cohorts in a third review (Wanders et al, 2019); a fourth showed no effect of PUFA on glucose or insulin for people with T2DM (Telle-Hansen, Gaundal, & Myhrstad, 2019); and a fifth found replacement of liquids oils with palm oil did not affect glucose or insulin levels (Zulkiply, Balasubramaniam, Bakar, Rashed, & Ismail, 2019). TFAs did not affect glucose or insulin (Aronis et al, 2012).…”
Section: Cardiovascular Outcomesmentioning
confidence: 99%